La nación en Colombia desde una perspectiva teórica (1810 y 1850) (2018)
ABSTRACT: The nation as an object of study for history, does not enjoy an unquestionable definition that agglomerates its political, social and imagined expressions. A conceptual limbo thus arises where anyone can speak of a nation without having a clear idea of its implications and manifestations, a situation that does not question the validity and capacity of the term to encompass the modern political and social content, or its legitimacy to sustain regimes. Thus, a vacuum is visible in Colombian historiography about what has been understood by nation and how the term has been transformed over time, therefore, the objective of this work is to specify from the conceptual history: What has been understood by nation in Colombia and its relationship with sovereignty and majesty, within the process of Spanish imperial disintegration that led to American independence and the construction of new republics?